Prefix Stripping Re-Re-Revisited: MEG Investigations of Morphological Decomposition and Recomposition - Stockall, Linnaea; Manouilidou, Christina; Gwilliams, Laura; Neophytou, Kyriaki; Marantz, Alec (Frontiers in Psychology, 2019)
We revisit a long-standing question in the psycholinguistic and neurolinguistic literature on comprehending morphologically complex words: are prefixes and suffixes processed using the same cognitive mechanisms? Recent work using MEG to uncover the dynamic temporal and spatial responses evoked by visually presented complex suffixed single words provide us with a comprehensive picture of morphological processing in the brain, from early, form-based decomposition, through lexical access, grammatically constrained recomposition, and semantic interpretation. In the present study, we find that MEG responses to prefixed words reveal interesting early differences in the lateralization of the form-based decomposition response compared to the effects reported in the literature for suffixed words, but a very similar post-decomposition profile. These results not only address a question stretching back to the earliest days of modern psycholinguistics, but also add critical support and nuance to our much newer emerging understanding of spatial organization and temporal dynamics of morphological processing in the human brain.